Comparison of the Morbidity after Laparoscopic Cholecystectomy for Acutely Inflamed Gall Bladder with and without Drain Insertion: A Randomized Controlled Trial - Hira Saleem, Aniqua Saleem, Ghulam Siddiq, Sharjeel Sarfraz Ahmed Sheikh, Huzaifa Saleem (Journal of Rawalpindi Medical College, 2021)
Abstract Objective: The study objective is to compare the pain frequency and mean hospital stay in patients with and without drain insertion, following laparoscopic cholecystectomy for acutely inflamed gallbladder. Methods: Randomized control trial was carried out in General Surgery Department Shifa International Hospital for a period of 1 year from October 2017 to October 2018. All patients with acutely inflamed gallbladder admitted underwent laparoscopic cholecystectomy using conventional 4 port method. Applying Lottery method patients were sorted into two groups; (Group A) – without drain and (Group B) – with drain. Post operatively parameters of pain and total hospital stay were assessed. Data was entered into a standard SPSS sheet version 15.0. Results: Mean age of patients in without drain (group A) was 52.00±14.84 years and in with drain (group B) was 47.50±18.28 years. In without drain (group A), there were 9 (30.0%) males and 21 (70.0%) females, mean VAS was 2.37±1.22, 16.7% (5 of 60 patients) had pain, and mean hospital stay was 1.93+/-0.79 days. In with drain (group B), 13 (43.3%) were males and 17 (56.7%) were females, mean VAS was 3.2 +/-1.36, 36.7% (11 of 60 patients) had pain and mean hospital stay was 3.17+/- 0.87 days. The difference between the two groups for mean VAS was significant (P<0.05), for mean hospital stay was significant (P<0.05) but for pain frequency was insignificant (P>0.05). Conclusions: It has been concluded that without drain, more appropriate results have been obtained as compared to drain. Clinical Trial Number: NCT04346550